The sale of Costa Rican companies to foreign investment: an academic perspective - Murillo Scott, Carlos (2013)
The School of Business and the Institute for Research on Economic Sciences of the University of Costa Rica, hereby present the most important results of the first phase of an exploratory work about the conditions affecting the dynamics of the selling of local capital companies to foreign companies or conglomerates, during the last 10 years (2002-2012). The present article deals with the perspective of a group of twenty five professors with varied amount of knowledge and experience in the field, which allows a preliminary approach to the matter, in this case, from the academic point of view. First hand experiences are also present in these initial results, due to the direct involvement of some of the participants in the buying-selling processes to which this work is referring. In this way, we offer the academic and other interested sectors, national and international, one first perception about this phenomenon and its relation with the role that it will probably play in the teaching processes of local schools of business and their impact on cultural, social, economic and academic development of the country.